Successful Oral Health Interventions for Children Living in Vulnerable Circumstances – A Scoping Review - Awani Balasooriyan; Christine Dedding; Clarissa Calil Bonifácio; Ruben R. Lacroix; Kirsten A. van Gelderen – Ziesemer; Rik Gerritsen; Monique H. van der Veen (International Dental Journal)
Promoting equal opportunities for young children’s oral health is a global health priority. Several interventions have been developed to address persistent oral health inequalities. However, the understanding of how these interventions improve children’s oral health remains limited. This scoping review aims to explore researchers’ explanations for the success of interventions promoting oral health in young children (≤5 years) and their families living in vulnerable circumstances in Western countries to strengthen future interventions. A comprehensive search strategy was developed and applied to three electronic databases: PubMed, Embase.com, and Clarivate Analytics/Web of Science Core Collection. This yielded 21,415 articles, which were screened according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidelines. The included articles were analysed thematically using a macro, meso, and micro system level framework. From a total of 21,415 references, 251 were assessed for eligibility; 39 articles were included, covering 37 interventions. In particular, interventions implemented at the macro level (n = 1), macro-meso levels (n = 4) and macro-meso-micro levels (n = 10) seem to be the most promising. The researchers argue that interventions with a personalised, educational and culturally sensitive approach, delivered through interdisciplinary collaboration between professionals within and outside the dental sector, supported by adequate resources (e.g., appropriate time, funding, location), are key to success. Future interventions require a careful account of families' complex daily realities by intensifying collaboration between parents, community workers, school staff, dental professionals, primary care providers and government, providing training and balanced workloads for professionals and ensuring sufficient resources. According to the researchers, engaging with actors from macro, meso, and micro system levels is essential in child oral health promotion. Government leadership is needed to address oral health inequalities as a societal responsibility in partnership with families, their social network, food shops, (pre-)schools, dental practices, community and primary care organisations.